2014
DOI: 10.1002/aoc.3112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, antitumor activity in mice, pharmacokinetics and tissue distribution in rats of di‐n‐butyl‐di‐(4‐chlorobenzohydroxamato)tin(IV) liposome

Abstract: Di‐n‐butyl‐di‐(4‐chlorobenzohydroxamato)tin(IV) (DBDCT) is an antitumor compound with high activity and relatively low bioavailability. In order to improve the pharmacokinetic characteristics and raise its therapeutic index, a liposome of DBDCT (DBDCT‐L) was prepared for the first time. A study of the pharmacokinetics and tissue distribution after intravenous administration of DBDCT‐L compared with free DBDCT to rats was investigated. DBDCT‐L showed a slower clearance, increased half‐time and a larger AUC valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…From the detailed literature survey on condensed heterocyclic ring systems, it is evident that indenopyrazoles have also played a significant role due to their wide biological activities, viz., analgesics, antitubercular, antiinflammatory agents, etc. An huge literature revealed that organotin(IV) complexes appeared as biologically potent moieties having antitumor [11,12], antitubercular [13][14][15], antifertility [16,17], antimicrobial [18][19][20], antiviral [21], antinematicidal, antiinsecticidal [22], antilieshmanial [23], anti-inflammatory [24], antidiabetic [25], antihypertensive [26], antioxidant [27], antimalarial [28] activity, etc. The bioactive metal complexes have enormous chemotherapeutic importance due to their ability to bind and degrade DNA of the microorganisms [29][30][31][32][33].…”
mentioning
confidence: 99%
“…From the detailed literature survey on condensed heterocyclic ring systems, it is evident that indenopyrazoles have also played a significant role due to their wide biological activities, viz., analgesics, antitubercular, antiinflammatory agents, etc. An huge literature revealed that organotin(IV) complexes appeared as biologically potent moieties having antitumor [11,12], antitubercular [13][14][15], antifertility [16,17], antimicrobial [18][19][20], antiviral [21], antinematicidal, antiinsecticidal [22], antilieshmanial [23], anti-inflammatory [24], antidiabetic [25], antihypertensive [26], antioxidant [27], antimalarial [28] activity, etc. The bioactive metal complexes have enormous chemotherapeutic importance due to their ability to bind and degrade DNA of the microorganisms [29][30][31][32][33].…”
mentioning
confidence: 99%